Nursing assistance systematization for the patient with pre–eclampsia - Aguiar, Maria Isis Freire de; Freire, Priscilla Brasileiro Galvão; Cruz, Isabella Marfisa Pessoa; Linard, Andréa Gomes; Chaves, Emília Soares; Rolim, Isaura Letícia Tavares Palmeira (Rev Rene, 2010)
Pre-eclampsia and eclampsia are diseases with high morbidity and mortality in pregnancy characterized by hypertension, proteinuria and/or swelling, having a high incidence and prevalence in Brazil. The aim of this research was to develop a form of Nursing Care System (NCS) to patients with Pre-eclampsia from the identification of nursing diagnoses (ND) of NANDA. This is a descriptive research conducted in a Maternity Teaching Hospital in the city of Fortaleza, Ceará, from April to May 2009, applying historical nursing on mothers with Pre-eclampsia. The results identified 11 ND. The most common are: risk of infection, acute pain, situational low self-esteem, excessive volume of fluid, nausea, sleep deprivation and risk of impaired liver function. We conducted care prescription based on classification of NIC. The study reflects the need to implement the NCS for the improvement of care, making it carefully differentiated, individualized and humanized.